Low Orbit Blues: The Noir in Cybersecurity - Balleste, Roy (Global Governance of Low Earth Orbit Satellites, 2025)
This chapter employs a metaphorical "noir" lens to critique the opaque and unpredictable cybersecurity risks of LEO satellite broadband. It explores the regulatory grey zones and asymmetries in enforcement that compromise resilience. Using literary and philosophical tools, the author reframes space-based internet as a new frontier of vulnerability, where state and non-state actors engage in a high-stakes struggle for digital control.